Successful strategies to increase the consumption of fruits and vegetables: results from the Danish ‘6 a day’ Work-site Canteen Model Study - Lassen, Anne; Thorsen, Anne Vibeke; Trolle, Ellen; Elsig, Mette; Ovesen, Lars (Public health nutrition, 2004)
To investigate changes in the consumption of fruits and vegetables in work-site canteens using the tools of continuous quality improvement, and to gain knowledge of practical strategies being effective in increasing the consumption. Study design included baseline data collection, an 8 h training session for all canteen staff, goal setting, strategy development and implementation for each canteen, end-point data collection and a follow-up data collection 4 months from the end-point (1 year from baseline). The main outcome measurement was average grams of fruits and vegetables per lunch meal served per customer (net weight; potatoes not included). Five workplaces in Denmark: a military base, an electronic component distributor, a bank, a town hall and a waste-handling facility. Work-site canteen managers, staff and customers. There were significant increases in the total consumption of fruits and vegetables for all five work-site canteens from baseline to end-point, 70 g per customer on average (67, 54, 39, 88 and 103 g, respectively). The follow-up data collection showed that the canteens either maintained or significantly increased consumption, the average increase being 95 g per customer compared with baseline (77, 60, 86, 70 and 183 g, respectively). This study demonstrates a large potential for work-site canteens to increase customers' intake of fruits and vegetables at lunch and suggests a broad spectrum of strategies to compose meals that are both rich in fruits and vegetables and attractive to customers.